Wetland science : perspectives from South Asia - Prusty, B. Anjan Kumar; Chandra, Rachna; Azeez, P. A. (Springer, 2017)
This book is an attempt to acknowledge the discipline 'wetland science' and to consolidate research findings, reviews and synthesis articles on different aspects of the wetlands in South Asia. The book presents 30 chapters by an international mix of experts in the field, who highlight and discuss diverse issues concerning wetlands in South Asia as case studies. The chapters are divided into different themes that represent broad issues of concern in a systematic manner keeping in mind students, researchers and general readers at large. The book introduces readers to the basics and theory of wetland science, supplemented by case studies and examples from the region. It also offers a valuable resource for graduate students and researchers in allied fields such as environmental studies, limnology, wildlife biology, aquatic biology, marine biology, and landscape ecology. To date the interdisciplinary field 'wetland science' is still rarely treated as a distinct discipline in its own right. Further, courses on wetland science aren't taught at any of the world's most prestigious universities; instead, the topics falling under this discipline are generally handled under the disciplines 'ecology' or under the extremely broad heading of 'environmental studies'. It is high time that 'Wetland Science' be acknowledged as an interdisciplinary sub-discipline, which calls for an attempt to consolidate its various subtopics and present them comprehensively. Thus, this book also serves as a reference base on wetlands and facilitates further discussions on specific issues involved in safeguarding a sustainable future for the wetland habitats of this region.
Keywords: Wetland ecology -- South Asia.; Wetland management -- South Asia.; South Asia.; elektronické knihy; electronic books